Bloomberg Sports : information overload goes abroad - Kealy, Patrick; Shastri, Yatin; Battistini, Francisco; Durrell, Tyler; Huh, Jeong; Agha, Nola (London : Human Kinetics, Inc., 2014)
Bloomberg Sports uses sports analytics to create advanced decision tools for professional teams and fantasy sports users. Their success in both the business and consumer markets stems from vital partnerships with Major League Baseball Advanced Media (MLBAM), Yahoo!, ESPN, and CBSSports. In a period of increased domestic competition, Bloomberg Sports is searching for the most appropriate international growth strategy. This expansion effort recently was aided by a new joint venture with IMG. By analyzing the market, industry, competitors, and products, important decisions can be made to help Bloomberg Sports expand and grow.
Originally published in Kealy, P., Sahstri, Y., Battistini, F., Durrell, T., Huh, J., & Agha, N. (2014). Bloomberg Sports: Information overload goes abroad. Case Studies in Sport Management, 3(1), 1-12. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Bloomberg Sports; Fantasy sports; Mass media and sports